Individual predictors of frequent emergency department use: a scoping review - Cynthia Krieg; Catherine Hudon; Maud-Christine Chouinard; Isabelle Dufour (BMC, 2016)
Abstract Background A small proportion of patients use an excessively large amount of emergency care resources which often results in emergency department (ED) overcrowding, decreased quality of care and efficiency. There is a need to better identify these patients in order to target those who will benefit most from interventions adapted to their specific needs. We aimed to identify the predictive factors of short-term frequent use of ED (over a 1-year period) and chronic frequent use of ED (over a multiple-year period) and to highlight recurring characteristics in patients. Methods A scoping review was performed of all relevant articles found in Medline published between 1979 and 2015 (Ovid). This scoping review included a total of 20 studies, of these, 16 articles focussed on frequent ED users and four others on chronic frequent ED users. Results A majority of articles confirm that patients who frequently visit the ED are persons of low socioeconomic status. Both frequent and chronic frequent ED users show high levels of health care use (other than the ED) and suffer from multiple physical and mental conditions. Conclusions This research highlights which individual factors predict frequent emergency department use. Further research is needed to better characterize and understand chronic frequent users as well as the health issues and unmet medical needs that lead to chronic frequent ED use.